The Correlation Between Physical Activity and Academic Performance in Teenagers (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Physical activity plays a crucial role in adolescent development, influencing both physical health and cognitive function. This study examines the correlation between physical activity levels and academic performance in teenagers, exploring how exercise impacts concentration, memory retention, and problem-solving abilities. Research suggests that students who engage in regular physical activity tend to demonstrate higher academic achievement compared to their sedentary counterparts. By analyzing various exercise patterns and academic outcomes, this study aims to provide valuable insights into the potential benefits of incorporating structured physical activity into educational programs. Understanding this correlation may lead to improved policies that promote a balanced approach to learning and well-being. This paper explores the relationship between physical activity and academic performance among teenagers. It examines various studies that suggest that regular physical engagement has a positive impact on cognitive function, concentration, and overall academic achievement. We highlight factors such as mental health, emotional well-being, and socio-economic influences that may mediate this relationship.